2022
DOI: 10.3389/fchem.2021.809415
|View full text |Cite
|
Sign up to set email alerts
|

Systematic kMC Study of Doped Hole Injection Layers in Organic Electronics

Abstract: Organic light emitting diodes (OLED) play an important role in commercial displays and are promising candidates for energy-efficient lighting applications. Although they have been continuously developed since their discovery in 1987, some unresolved challenges remain. The performance of OLEDs is determined by a multifaceted interplay of materials and device architectures. A commonly used technique to overcome the charge injection barrier from the electrodes to the organic layers, are doped injection layers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The resulting all-particle trajectories allow a detailed analysis of spatially resolved and material specific distributions of loss processes, as well as their dependency on material properties. (15,26,27,34). Details of the approach can be found in the references accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting all-particle trajectories allow a detailed analysis of spatially resolved and material specific distributions of loss processes, as well as their dependency on material properties. (15,26,27,34). Details of the approach can be found in the references accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome the obstacles like limited charge carrier concentration or insufficient charge balance in the device due to large hole injection barriers, doping HILs is a proven technique [ 51 ]. Doped materials can be roughly classified into three categories: polymer materials, transition metal oxide materials, metal and metal compound materials.…”
Section: Doped Hole Injection Layermentioning
confidence: 99%
“…Currently, the models in the literature describing the doping physics for disordered organic semiconductors focus mostly on charge-neutral systems [8][9][10][11][12][13][14]. Experimentally, it has been shown that the charge-carrier mobility in homogeneous disordered organic semiconductors depends on the temperature, the electric field, and the charge-carrier concentration [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, three-dimensional (3D) discrete lattice models with a Gaussian density of states (DOS) and threedimensional kinetic Monte Carlo (3D-KMC) simulation techniques of localized charge-carrier dynamics were developed [21][22][23][24][25][26]. These models can successfully explain measured electrical characteristics of OLEDs and have recently been applied to study the physics of molecularly doped systems [9][10][11][12][13][14]. From these simulation studies, it was found that a released charge carrier is not completely free to move, but stays at a nearby host molecule.…”
Section: Introductionmentioning
confidence: 99%